2012
DOI: 10.1186/1471-2229-12-146
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of small non-coding RNAs from Chinese fir by high throughput sequencing

Abstract: BackgroundSmall non-coding RNAs (sRNAs) play key roles in plant development, growth and responses to biotic and abiotic stresses. At least four classes of sRNAs have been well characterized in plants, including repeat-associated siRNAs (rasiRNAs), microRNAs (miRNAs), trans-acting siRNAs (tasiRNAs) and natural antisense transcript-derived siRNAs. Chinese fir (Cunninghamia lanceolata) is one of the most important coniferous evergreen tree species in China. No sRNA from Chinese fir has been described to date.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 63 publications
8
72
1
Order By: Relevance
“…The apparent lack of DCL3 and the low frequency of 24-nt sRNAs are not features common to all conifers, as it was recently shown that Cunninghamia lanceolata has an sRNA distribution more similar to angiosperm species, including a large fraction of 24-nt sRNAs (Wan et al, 2012). They also reported the presence of sequences predicted to code for proteins necessary for the biogenesis of 24-nt sRNAs, including DCL3.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent lack of DCL3 and the low frequency of 24-nt sRNAs are not features common to all conifers, as it was recently shown that Cunninghamia lanceolata has an sRNA distribution more similar to angiosperm species, including a large fraction of 24-nt sRNAs (Wan et al, 2012). They also reported the presence of sequences predicted to code for proteins necessary for the biogenesis of 24-nt sRNAs, including DCL3.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on sRNA studies in gymnosperm seeds have been lacking so far, but previous work on conifer sRNAs have reached different and contradicting conclusions regarding the presence of 24-nt sRNAs, typically associated with hetsiRNAs, in the sRNA transcriptome of the conifers clade Morin et al 2008;Lee et al 2011;Chávez-Montes et al 2014;Wan et al 2012;Zhang et al 2012bZhang et al , 2013bNystedt et al 2013;Niu et al 2015). In somatic embryo-derived material from the conifer Japanese larch (Larix leptolepis) the presence of significant amounts of 24-nt sRNAs has been reported (Zhang et al 2012b(Zhang et al , 2013b, but it would be interesting to check for the presence of these sRNAs in conifer seeds.…”
Section: Abundance Of Small Rnas In Seed Tissuesmentioning
confidence: 99%
“…There has been conflicting evidence about the presence of 24-nucleotide short RNAs (sRNAs) in gymnosperms [26][27][28][29] , a class of sRNA that silence transposable elements by the establishment of DNA methylation 30 . Across 22 samples, we identified numerous 24-nucleotide sRNAs, but these were highly specific to reproductive tissues, largely associated with repeats but present at substantially lower levels than in angiosperms ( Fig.…”
Section: Presence Of Long Introns and Gene-like Fragmentsmentioning
confidence: 99%